Answered

At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Discover detailed solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

sinθ- cosθ+1 / sinθ+cosθ-1 = 1/secθ-tanθ​

Sagot :

Step-by-step explanation:

We know that

sin² θ+ cos² θ = 1

¶ cos² θ = 1 - sin² θ

→cos θ × cos θ = (1+sin θ)(1-sin θ)

→cos θ/(1-sin θ) = (1+sin θ)/cos θ

By the property of equal ratio

→cos θ/(1-sin θ) = (1+sin θ)/cos θ =

(1+sin θ-cos θ) /( cos θ- 1+ sin θ)

→cosθ/(1-sinθ) = (1+sinθ-cosθ)/(cosθ- 1+sinθ)

→cosθ/(1-sinθ) = (sinθ-cosθ+1)/(cosθ+sinθ-1)

On dividing LHS by cos θ

→(cos θ/cos θ)/(1- sin θ)/cos θ) =

(sinθ-cosθ+1)/(cosθ+sinθ-1)

→1/(1- sin θ)/cos θ) = (sinθ-cosθ+1)/(cosθ+sinθ-1)

→1/(1/Cos θ)-(Sin θ/ cos θ) =

(sinθ-cosθ+1)/(cosθ+sinθ-1)

→1/(secθ-tanθ) = (sinθ-cosθ+1)/(cosθ+sinθ-1)

→RHS = LHS

Additional comment:

If a/b = c/d then a/b = c/d

= (a+c)/(b+d)

Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.